STRATEGI GURU DAN ORANG TUA MENINGKATAN MOTIVASI BELAJAR PADA SISWA YANG MALAS BELAJAR DAN MENGERJAKAN TUGAS DI SD SWASTA HKBP SIBORORONGBORONG - Wilson Simanjuntak; Yohana Sri Imelda Situmorang; Ester Gusseni Purba; Castia Patricia Simanjutak; Miranda Ester Nababan; Joel Wenpriko Manalu; Gracela Yohana Purba (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This research aims to implement various Class 23 Teaching Campus Programs to identify problems that exist in elementary schools. The method used is descriptive qualitative with data collection techniques through interviews and observation. This research was carried out at HKBP Siborongborong Private Elementary School on April 26 2024. The research targets were grade VI students. Data collection was carried out through direct observation and interviews. The research results show that the Teaching Campus program, such as teaching assistance, learning mathematical multiplication, operating integers with TTS learning media, learning technology-based English, learning the Koran, learning STEM (Science, Technology, Engineering, and Mathematics), using Search learning media Words, Indonesian TTS, and technology adaptation can increase students' learning motivation. However, there are obstacles and challenges during implementation, especially in online learning, so teachers need to have various alternatives to ensure a smooth learning process.